STATE MEASURES ON ORGANIZATION OF INTERACTION BETWEEN INSTITUTIONS OF PROFESSIONAL EDUCATION AND EMPLOYERS - Vladimir V. Mironov; Evgeny P. Ilyasov; Valery A. Gurtov (Высшее образование в России)
Successful employment of graduates can be considered as a result of effective cooperation between educational institutions and employers. It can be ensured due to the necessary contents of the basic professional educational programs and high quality of graduates’ training. The article considers the existing measures aimed at better interaction between educational institutions and employers and the steps additionally taken by the Ministry of Education and Science of the Russian Federation.